1983
DOI: 10.1055/s-2008-1054750
|View full text |Cite
|
Sign up to set email alerts
|

Verbesserung der Differentialdiagnose pigmentierter Veränderungen am Augenhintergrund mit Hilfe der multispektralen Bildanalyse*

Abstract: On the basis of preliminary investigations completed in 1978 dealing with computer-assisted analysis of infrared photographs of the ocular fundus, multispectral photograph analysis methods were tested as to their usefulness in improving differential diagnosis. The computer used in this case was a process control computer with special peripheral equipment. Computer programs were developed to solve problems relating to photograph analysis and classification. Information obtained by computer processing should pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…At the redshift of the protocluster the Balmer and 4000 Å break falls within the J 110 filter, therefore we can make a simple colour cut to select candidate red protocluster galaxies. Zirm et al (2008) show that there is a significant overdensity of galaxies in this protocluster field with colours 1.1 < J 110 – H 160 < 2.1. Using the same colour cut we identify seven red galaxies (galaxies 1, 2, 4, 12, 13, 14 and 16), two of which are also Hα emitters.…”
Section: Selecting Protocluster Galaxiesmentioning
confidence: 78%
See 2 more Smart Citations
“…At the redshift of the protocluster the Balmer and 4000 Å break falls within the J 110 filter, therefore we can make a simple colour cut to select candidate red protocluster galaxies. Zirm et al (2008) show that there is a significant overdensity of galaxies in this protocluster field with colours 1.1 < J 110 – H 160 < 2.1. Using the same colour cut we identify seven red galaxies (galaxies 1, 2, 4, 12, 13, 14 and 16), two of which are also Hα emitters.…”
Section: Selecting Protocluster Galaxiesmentioning
confidence: 78%
“…The protocluster was also observed with Near Infrared Camera and Multi‐Object Spectrometer (NICMOS) camera 3 on HST for three orbits though each of the F110W ( J 110 ) and F160W ( H 160 ) filters. Further discussion of the NICMOS observations can be found in Zirm et al (2008).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is surrounded by a diffuse UV halo which is evidence for in situ star formation outside the main RG (Hatch et al 2008). Furthermore, the field has been shown to harbour overdensities in both Lyα and Hα emitting galaxies, extremely red objects (EROs), X‐ray emitters and submillimetre bright galaxies (Pentericci et al 2000; Stevens et al 2003; Kurk et al 2004b,a; Croft et al 2005; K07; Zirm et al 2008). Kurk et al (2004b) has also shown that the EROs and Hα emitting galaxies are located closer to the RG than the bluer star‐forming galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…Zirm et al (2008) have shown that the 1138 system contains red galaxies, some of which might be quiescent. However, the red sequence is still in the stages of formation and has not been properly established yet.…”
Section: Discussionmentioning
confidence: 99%